Special issue. - Sarat, Austin (Emerald, 2014)
In The beautiful prison incarcerated Americans and prison critics seek to imagine the prison as something better than a machinery of suffering. From personal testimony to theoretical meditation these writers explore and confront the practical and cultural limits the prison places on its transformation into a socially constructive institution.
Includes index.
Keywords: Social Science -- Criminology.; Prisons.; Law & society.; Penology & punishment.; Prisons -- United States.; Imprisonment -- United States.; elektronické knihy; electronic books